INFLUENCE OF NEGATIVE PEER PRESSURE AND SUBSTANCE ABUSE ON ANTISOCIAL BEHAVIOUR: THE MODERATING ROLE OF RESILIENCE AMONG SECONDARY SCHOOL STUDENTS IN KEFFI, NASARAWA STATE, NIGERIA - Yusuf, Kemi Agana; Alhassan, Emmanuel Onu; Tafida, Abubakar Musa; Kenku, Akeem; Nalah, Augustine Bala; Abubakar, Suleiman Aliyu; Daniel, Enoch (African Journal of Social and Behavioural Sciences, 2025)
This study examined the influence of negative peer pressure and substance abuse on antisocial behavior: the moderating role of resilience among secondary school students in Keffi, Nasarawa State, Nigeria. A sample of two hundred and seventy (270) students was used for the study. The participants’ ages ranged from 13 to 18 years, with 52.25% being female and 43.75% being male. The participants were administered the WHO Youth Drug Survey, the Peer Influence Scale Questionnaire-Revised, the Subtypes of Antisocial Behavior Questionnaire, and the Nicholson McBride Resilience Questionnaire. The study used a survey research design and multiple linear regressions for data analysis. The first hypothesis was accepted, indicating a significant prediction between negative peer pressure and antisocial behaviour among secondary school students in Keffi, Nasarawa State, Nigeria. Also, the second hypothesis was also accepted, indicating a significant prediction between substance abuse and antisocial behaviour among secondary school students in Keffi, Nasarawa State, Nigeria. Furthermore, hypothesis three was also accepted, indicating a joint significant prediction between negative peer pressure and substance abuse on antisocial behaviour. Similarly, Hypothesis four was tested, and the result showed that resilience moderates the relationship between negative peer pressure and antisocial behaviour. Lastly, the fifth hypothesis was accepted, indicating a significant moderation between substance abuse and antisocial behaviour. It is therefore recommended that the government should incorporate resilience-training programmes into the school curricula. Such programmes can include life skills education, emotional regulation training, problem-solving workshops, and peer mentoring schemes.